2008
DOI: 10.1002/pip.843
|View full text |Cite
|
Sign up to set email alerts
|

Chemical incorporation of copper into indium selenide thin‐films for processing of CuInSe2 solar cells

Abstract: A chemical method of incorporating copper into indium selenide thin‐films has been investigated, with the goal of creating a precursor structure for conversion into CuInSe2 (CIS) layers suitable for solar cell processing. The precursor and converted layers have been investigated with scanning electron microscopy (SEM), X‐ray diffraction (XRD), Raman spectroscopy and X‐ray photoelectron spectroscopy (XPS). From these measurements, the incorporation of copper into the indium selenide layers is concluded to proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…Confirmation of Cu 2-x Se compounds by XRD is difficult for these layers as the main Cu 2-x Se diffraction peaks overlap with the main peaks from the IGS patterns. Since a definite phase composition could not be determined for the precursor layers, it is not possible to propose a detailed reaction mechanism for the incorporation of Cu as was possible for previous work with Ga-free precursor layers [9]. Many more diffraction peaks are observed after annealing at 250°C in the presence of Se (C), all of which can be associated with copper selenide phases with higher Se content and the general formula CuSe y (1 ≤ y ≤2) (JCPDS 49-1457, 83-1814 and 19-0400).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirmation of Cu 2-x Se compounds by XRD is difficult for these layers as the main Cu 2-x Se diffraction peaks overlap with the main peaks from the IGS patterns. Since a definite phase composition could not be determined for the precursor layers, it is not possible to propose a detailed reaction mechanism for the incorporation of Cu as was possible for previous work with Ga-free precursor layers [9]. Many more diffraction peaks are observed after annealing at 250°C in the presence of Se (C), all of which can be associated with copper selenide phases with higher Se content and the general formula CuSe y (1 ≤ y ≤2) (JCPDS 49-1457, 83-1814 and 19-0400).…”
Section: Resultsmentioning
confidence: 99%
“…Ionexchange methods are attractive due to the simplicity and low cost of the equipment required and the low temperatures employed (relative to vacuum deposition techniques). We have shown previously that copper can be incorporated into In 2 Se 3 layers from solution via such an ion-exchange process and that the resulting precursor structure can be converted into chalcopyrite CuInSe 2 (CIS) by annealing [9]. Solar cells based on CIS layers are not able to reach the same high efficiencies as those based on CIGS and so in this work we report the incorporation of Cu ions into indium gallium selenide (IGS) thin films and present characterisation of the precursor and annealed layers.…”
Section: Introductionmentioning
confidence: 99%
“…CdS, belonging to II-VI groups, is one of the promising semiconductors, having bulk bandgap 2.42 eV. It also acts as window layer in CdTe [4] and copper indium (di) selenide [5] as well as copper indium gallium (di) selenide [6] based solar cells. But the disadvantage of CdS is that it degrades into soluble cadmium cations under PEC conditions which are hazardous [7].…”
Section: Introductionmentioning
confidence: 99%
“…When In2Se3 layers were immersed in hot, aqueous, acidic copper sulphate solution it was found that copper was incorporated into the layers as CU2Se [4]. The composition of a set of such layers as measured by EDX before and after annealing with Se vapour is shown in Fig.…”
Section: Vs Agmentioning
confidence: 99%
“…These CIGS layers are deposited using expensive, high-vacuum equipment and it is expected that reductions in the cost of CIGS-based photovoltaics (PV) could be achieved by moving to simpler, non-vacuum based deposition techniques. Many such techniques have been investigated [3] and we have previously reported the use of an ion-exchange reaction as a step in the formation of a precursor layer suitable for conversion into CulnSe2 (CIS) [4]. Similar reactions have been applied to other thin-film PV applications, including formation of CU2S-CdS structures, In2S3 and CulnS2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%